Sequential analysis by immunoprecipitation-MALDI-TOF: a novel method for detection and identification of alloantibody specificities - Heinold, Andreas; Kuehl, Boris; Brenner-Weiß, Gerald; Opelz, Gerhard; Tran, Thuong Hien (Human immunology, 2010)
Alloantibodies are known to influence transplant outcomes. Apart from human leukocyte antigens (HLA), non-HLA targets have been suggested to play a significant role, but little is known about their nature. Here, we present a novel method for identification and characterization of cell surface antigens bound by alloreactive antibodies. Our method consists of 2 consecutive steps: first, immunoprecipitation of cell surface proteins is carried out with serum and, second, matrix-assisted laser desorption/ionization-time-of-flight is used to fingerprint the precipitated cell-surface proteins. As an example, we performed immunoprecipitation with peripheral blood lymphocytes, which had been incubated with an alloreactive serum; immune complexes were coupled to protein-G beads and separated by sodium dodecyl sulfate-polyacrylamide gel electrophoresis; differential protein fractions were then analyzed by matrix-assisted laser desorption/ionization-time-of-flight. The method was validated with serum as well as with plasmapheresis material, which contained antibodies of known HLA specificities, demonstrating its applicability for clinical use.
Gesehen am 02.06.2021